Nil by Mouth - Oldman, Gary; Oldman, Gary; Fortunato, Ron; Winstone, Ray; Burke, Kathy; Creed-Miles, Charlie (BFI, 2022)
Gary Oldman's debut as writer/director is so uncompromisingly honest, it makes other portraits of working-class life look like sour caricature or misplaced idealism. Oldman grew up in south east London, the setting for this tale of macho violence, drunkenness, drug addiction and petty crime, and very clearly knows what he's talking about. He's helped, of course, by stunning performances from his entire cast, most notably Winstone as the volatile but self-pitying Ray, given to beating up his long-suffering wife (Kathy Burke) and threatening her irresponsible junkie brother (Charlie Creed-Miles). There's no sermonising or romanticising here, just a sad, clear-eyed acknowledgement that domestic abuse and crime create a vicious circle from which many barely even try to escape. Shot and scripted in a deceptively casual, bleakly 'realist' style, it's the closest Britain has produced to a Cassavetes film, and as such, profoundly humane. [www.timeout.com]